2022
DOI: 10.19173/irrodl.v23i3.6201
|View full text |Cite
|
Sign up to set email alerts
|

Doing Open Science in a Research-Based Seminar: Students’ Positioning Towards Openness in Higher Education

Abstract: This study investigates undergraduate students’ attitudes towards and experiences with open education practices (OEP) in a research-based linguistics seminar. Data was collected through written assignments in which two groups of students in subsequent terms were surveyed on their willingness to publish (a) academic posters in open access (OA); (b) teaching concepts as open educational resources (OER); and (c) personal reflections on the research process in OA. Through qualitative data analysis, we examine stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[ 108 ] also identified that key benefits, in terms of student attitudes, were for transparency, collaboration and research progress. Truan & Dressel [ 109 ] also investigated attitudes towards and experiences of students with practices of open education, through a seminar about research-based linguistics. Students ( n = 59) produced written narratives and then completed a quantitative survey on (i) their willingness to upload and publish academic-based posters in an open access format, (ii) teaching concepts in the form of open educational resources and (iii) their own reflections on their personal experience of engaging with open access publishing.…”
Section: Open and Reproducible Scholarship And Students' Attitudes To...mentioning
confidence: 99%
“…[ 108 ] also identified that key benefits, in terms of student attitudes, were for transparency, collaboration and research progress. Truan & Dressel [ 109 ] also investigated attitudes towards and experiences of students with practices of open education, through a seminar about research-based linguistics. Students ( n = 59) produced written narratives and then completed a quantitative survey on (i) their willingness to upload and publish academic-based posters in an open access format, (ii) teaching concepts in the form of open educational resources and (iii) their own reflections on their personal experience of engaging with open access publishing.…”
Section: Open and Reproducible Scholarship And Students' Attitudes To...mentioning
confidence: 99%
“…In other words, these participants overcame the challenges faced in the classroom by creatively designing posters to explain critical concepts for presentations either as a group or individually. For S1, it is believed that what the learner sees in the class can be easily remembered; hence they designed a poster where pictures related to content were drawn and shared with learners; this is supported by (Truan & Dressel, 2022), posit that poster as teaching aid have several benefits to learners; it motivates the learner to learn, helps them to focus while catching and fun, makes content understandable, and is it retains the information, to mention but few. Additionally, in the case of S3, they use visual aids such as pictures and charts to navigate the challenges faced in the class.…”
Section: S3: To Teach I Had To Use a Lot Of Visual Aids Like Pictures...mentioning
confidence: 99%
“…online courses [110],Pedagogical reform [110],innovative solutions [110],research-based learning [111],multi-perspective views [112],thoughtful thinking [113],polylogical research [110],transparency [114],democratically oriented [115],transparency and awareness [116],reorganisation of academic tribes [117],digitization [118],Scientific Revolutions [119],Open Scholar [120],open educators [121],Open designer [121],OER expert [121],open Assessment [121],Reuse [122], Revise [122], Remix [122], Retain [122],and Redistribute [122],; The Open University [123];The Open Classroom [125]; Open Courseware [124]; Open Education [123]…”
Section: Page 605mentioning
confidence: 99%